UNDERSTANDING PUBERTY EDUCATION AS A SELF PROTECTION MEASURE FOR PRIMARY ELEMENTARY SCHOOL - Durrina, Ashfiyatu; Kamalia, Durratun Nafiisah; Huda, Ibti Halul (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
Children at elementary school age experience critical developmental periods, including puberty which is a transition phase towards adulthood. Children at this stage tend to be vulnerable to various risks, such as bullying, sexual harassment, and promiscuity. Efforts to protect oneself during puberty involve providing accurate information and correct understanding regarding changes in the body, emotions, and reproductive health. Providing Puberty Education to elementary school-age children is considered timely and relevant because it can equip them with the necessary knowledge. This research aims to provide understanding to elementary school-age children facing the puberty phase and provide guidance to educators, parents, and related parties in increasing understanding of Puberty Education in elementary school-age children. This research aims to provide understanding to elementary school-age children and guidance to parents and teachers in dealing with puberty in children. This research uses qualitative research with a case study type of research. The research subjects were students and teachers. The data collection techniques used were interviews, observation, and content analysis. The results of this research show that Puberty Education can bring positive changes in children's understanding when experiencing the puberty phase. Puberty Education is also important to know how to protect yourself from sexual harassment and promiscuity. This Puberty Education Program can also be used as a guide to protect children from potential risks and challenges and can foster a healthy understanding in dealing with developments during the puberty phase